Analysis of population structure and genetic diversity reveals gene flow and geographic patterns in cultivated rice (O. sativa and O. glaberrima) in West Africa - Yelome, O.I.; Audenaert, K.; Landschoot, S.; Dansi, A.; Vanhove, W.; Silué, D.; Damme, P. van; Haes, G. (Springer, 2018)
To fully exploit the diversity in African rice germplasm and to broaden the gene pool reliable information on the population genetic diversity and phenotypic characteristics is a prerequisite. In this paper, the population structure and genetic diversity of 42 cultivated African rice (Oryza spp.) accessions originating from West Africa (Benin, Mali and Nigeria, Liberia etc.) were investigated using 20 simple sequence repeats (SSR) and 77 amplified fragment length polymorphisms (AFLP). Additionally, field trials were set up to gain insight into phenotypic characteristics that differentiate the genetic populations among rice accessions. The analysis revealed considerably high polymorphisms for SSR markers (PIC mean = 0.78) in the germplasm studied. A significant association was found between AFLP markers and geographic origin of rice accessions (R = 0.72). Germplasm structure showed that Oryza sativa accessions were not totally isolated from Oryza glaberrima accessions. The results allowed identification of five O. glaberrima accessions which grouped together with O. sativa accessions, sharing common alleles of 18 loci out of the 20 SSR markers analyzed. Population structure analysis revealed existence of a gene flow between O. sativa and O. glaberrima rice accessions which can be used to combine several interesting traits in breeding programs. Further studies are needed to clarify the contributions of this gene flow to valuable traits such as abiotic and biotic stresses including disease resistance.